2021
DOI: 10.1002/ejic.202100079
|View full text |Cite
|
Sign up to set email alerts
|

Bis(8‐hydroxyquinoline) Ligands: Exploring their Potential as Selective Copper‐Binding Agents for Alzheimer's Disease

Abstract: Amyloid-β (Aβ) aggregation, metal ion dyshomeostasis, and oxidative stress are pathological features of Alzheimer's disease (AD). Aβ and metal ions form metal-Aβ complex species that influence the aggregation of Aβ and, in particular, redox metal ions such as Cu lead to the production of reactive oxygen species (ROS). To target metal coordination to Aβ and the reactivities of CuÀ Aβ, metal chelating agents must extract Cu 2 + from Aβ in AD pathological conditions. Bis(8-hydroxyquinoline) ligands can extract Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Recently, Oliveri reported a novel bis-8HQ ligand (compound 2) with promising in vitro anti-Aβ activity and good drug-like properties. 13 The study demonstrated that the compound 2 was able to chelate Cu 2+ accumulated in the Aβ plaque (both in the absence and presence of Zn 2+ ) which could address the loss of Cu homeostasis in the AD-mimic condition with the presence of excessive Zn 2+ , which may be due to the higher selectivity of the compound toward Cu 2+ . This indicated that the compound 2 is promising for protection against ROS-induced damages in the Zn-rich AD brain.…”
Section: Figure 6 8hq-based and 8hq-inspired Copper Chelators As Anti...mentioning
confidence: 91%
See 3 more Smart Citations
“…Recently, Oliveri reported a novel bis-8HQ ligand (compound 2) with promising in vitro anti-Aβ activity and good drug-like properties. 13 The study demonstrated that the compound 2 was able to chelate Cu 2+ accumulated in the Aβ plaque (both in the absence and presence of Zn 2+ ) which could address the loss of Cu homeostasis in the AD-mimic condition with the presence of excessive Zn 2+ , which may be due to the higher selectivity of the compound toward Cu 2+ . This indicated that the compound 2 is promising for protection against ROS-induced damages in the Zn-rich AD brain.…”
Section: Figure 6 8hq-based and 8hq-inspired Copper Chelators As Anti...mentioning
confidence: 91%
“…Some multifunctional Cu chelators without anti-Aβ effect were reported (compounds 13-16). 8HQpiperidine compound (13) showed good metal chelating property, antioxidant activity (DPPH IC50 = 544 μM) and inhibitory effects agaisnt both human AChE (% inhibition = 75.8%) and BuChE (IC50 = 11.11 nM). 109 Compound with similar AChE inhibitory effect such as 8HQ-tacrine 14 (AChE inhibitor) hybrid was developed.…”
Section: Figure 6 8hq-based and 8hq-inspired Copper Chelators As Anti...mentioning
confidence: 99%
See 2 more Smart Citations
“… 8 The process of Aβ aggregation can trigger the production of intra- and extra-cellular reactive oxygen species (ROS), which can lead to oxidation and cellular damage. 9 In addition, neurotoxicity was induced by Aβ oligomers and fibrils through binding to the plasma membrane, resulting in metabolic dysfunction and neuronal cell death. 10 Therefore, the inhibition of Aβ fibrillation, the disintegration of mature Aβ aggregates, and the promotion of the clearance of Aβ to maintain the balance of the metabolism and catabolism of Aβ appear to be quite significant for the prevention and treatment of AD.…”
Section: Introductionmentioning
confidence: 99%